- Relationship Between Support And Motivation With Adherence To Antiretroviral (ARV) Use In Preventing Mother-To-Child Transmission Of HIV (PPIA) : Literature Review: - - Aryani, Ajeng Nita; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
The rate of HIV transmission from mother to baby is still very high in the world, even in Indonesia. Antiretroviral (ARV) use is the most effective treatment for preventing HIV transmission from mother to baby. However, there are many factors that make pregnant women disobedient in treatment, one of the factors is the lack of support and motivation. The method used in this study was a literature study to find out whether support and motivation had a major impact on maternal adherence in taking ARVs. The results obtained were that motivation and support from the family, especially the husband, greatly influenced the mother's adherence to using ARVs, so that support and motivation played a very important role in preventing HIV transmission from mother to child (PPIA).